Percutaneous cystolitholapaxy in reconstructed bladder through the bowel segment - Razan Khalid Almesned; Abdulrahman Binjawhar; Waleed Altaweel; Mohammed Alomar (Urology Annals)
Introduction: Calculous formation is a well-known complication of lower urinary tract reconstruction using an intestinal segment. Special considerations are required as access to the reconstructed bladder is complicated. To date, a standard strategy is yet to be accepted. Objective: This study aims to investigate the efficiency and safety of percutaneous cystolitholapaxy (PCCL) access. Materials and Methods: This was a retrospective analysis of patients with reconstructed lower urinary tract who developed bladder stones and were treated with PCCL. Results: Seven patients underwent a total of nine PCCLs between 2019 and 2023. Sone burden ranged from 4 to 10 cm. No intraoperative complications were faced. Three patients had residual stone fragments < 7 mm in size. Suprapubic catheter was removed between days 0 and 3 postoperative. Cystostomy was left to close spontaneously, none of the patients developed peritoneal leak after removal. Patients with Mitrofanoff channel reported no leak or compromise to the continued mechanism. Predominant stone composition was magnesium ammonium phosphate (struvite) in seven cases. Conclusion: In our experience, PCCL accessing through bowel segment without tract closure in reconstructed bladder is a reliable and safe approach. When it comes to our patient selection, no limitations to this approach have been identified.